2021
DOI: 10.1111/andr.13128
|View full text |Cite
|
Sign up to set email alerts
|

A higher preconceptional paternal body mass index influences fertilization rate and preimplantation embryo development

Abstract: Background: Obesity is a worldwide problem affecting the health of millions of people throughout the life course. Studies reveal that obesity impairs sperm parameters and epigenetics, potentially influencing embryonic development.Objective: To investigate the association between preconceptional paternal body mass index (BMI) and embryo morphokinetics using a time-lapse incubator and in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) outcomes. Materials and methods:Participants were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Finally, 19 remaining studies were included in the analysis. Table 1 summarizes the details of the studies included in the review 36–54 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 19 remaining studies were included in the analysis. Table 1 summarizes the details of the studies included in the review 36–54 …”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the details of the studies included in the review. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] A total of 13 included studies were retrospective in design and the remaining 6 were prospective studies. Majority of the studies were conducted in China (n = 5) and United States (n = 4) followed by Turkey (n = 2) and Denmark (n = 2).…”
Section: Selection Of Articles Study Characteristics and Quality Of I...mentioning
confidence: 99%
“…suggested that male BMI was not related to sperm parameters ( 31 , 32 ), but it did affect embryo quality, and led to bad pregnancy outcomes ( 20 , 27 , 32 35 ). Conversely, the results of other studies suggested that BMI did not affect in vitro fertilization, embryo development and quality, pregnancy outcomes, and obstetric outcomes ( 24 , 30 , 31 , 33 , 36 – 38 ).…”
Section: Introductionmentioning
confidence: 86%
“…Fertilization rate, total usable embryos and implantation potential were not affected by maternal obesity Hoek et al [3] 211 couples Paternal (adjusted for maternal BMI) Weight and height measured (for both men and women)…”
Section: Referencesmentioning
confidence: 98%